2017
DOI: 10.1016/j.jmaa.2017.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic semigroups from second order partial differential equations

Abstract: Abstract. We give general conditions on given parameters to ensure Devaney and distributional chaos for the solution C 0 -semigroup corresponding to a class of second-order partial differential equations. We also provide a critical parameter that led us to distinguish between stability and chaos for these semigroups. In the case of chaos, we prove that the C 0 -semigroup admits a strongly mixing measure with full support. We also give concrete examples of partial differential equations, such as the telegraph e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In contrast to the recent research studies of J. A. Conejero, C. Lizama et al [6]- [8], where the authors have studied the hypercyclic and chaotic solutions of certain kinds of abstract second and third order differential equations in the spaces of Herzog analytic functions by employing, primarily, the Desch-Schappacher-Webb criterion [10], the operator matrix under our consideration is not bounded and as such does not generate a strongly continuous semigrop on E n a priori. This is the main reason why we use the theory of C-regularized semigroups in this paper.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…In contrast to the recent research studies of J. A. Conejero, C. Lizama et al [6]- [8], where the authors have studied the hypercyclic and chaotic solutions of certain kinds of abstract second and third order differential equations in the spaces of Herzog analytic functions by employing, primarily, the Desch-Schappacher-Webb criterion [10], the operator matrix under our consideration is not bounded and as such does not generate a strongly continuous semigrop on E n a priori. This is the main reason why we use the theory of C-regularized semigroups in this paper.…”
Section: Introductionmentioning
confidence: 73%
“…also [17,Theorem 2.10.45] for a generalization of the above-mentioned theorem to abstract time-fractional differential equations). In our approach, we almost always face the situation Ẽ = E n , which indicates a certain type of subspace frequent hypercyclicity of constructed solutions to (ACP n ) (in [6]- [8], the situation in which Ẽ = E n can really occur). At the end of paper, we provide several examples and applications of our results.…”
Section: Introductionmentioning
confidence: 99%
“…Since PDEs have numerous types, it is difficult to give a particular definition of chaos that is consistently significant for the bulk of PDE. A lot of research has been done in the field of chaos analysis for PDEs [1][2][3][4][5][6][7][8][9]. Knoblock et al [1] showed a transition from periodic oscillations to chaos using the two-dimensional thermosolutal convection numerical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Stability analysis for a class of PDE chaotic models is introduced by Xiang et al [3]. Conejero et al [4] provided broad criteria on parameters to guarantee Devaney and distributional chaos for the semigroup solution corresponding to a class of second order PDE. Chaotic models for neural PDE were established [5].…”
Section: Introductionmentioning
confidence: 99%
“…Particular attention deserves the case of C 0 -semigroups of operators, since many of them are originated in the analysis of the asymptotic behaviour of solutions to certain linear partial differential equations and to infinite systems of linear differential equations. Especially, different notions of chaos for C 0 -semigroups have experienced a great development in recent years (see, e.g., [1,2,5,16,22,23,24,25,27,29,38,46,48]).…”
Section: Introductionmentioning
confidence: 99%